2020
DOI: 10.5435/jaaos-d-20-00944
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Hemoglobin A1c >7.5 Is Associated With Increased Bundled Payment Costs in Total Hip and Knee Arthroplasties

Abstract: Introduction: Studies have shown that patients with diabetes mellitus are at an increased risk for complications and higher episode-of-care costs after total hip (THA) and total knee arthroplasties (TKA), but the effect of poor glycemic control on episode-of-care costs has yet to be addressed in the literature. The purpose of this study was to determine whether patients with a higher preoperative hemoglobin A1c have increased episode-of-care costs in diabetic patients undergoing THA and TKA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…A preoperative HbA1c of less than 7.850%, with postoperative HbA1c less than 6.650%, preoperative blood glucose less than 130.50 mg/dL, and postoperative blood glucose of less than 148.5 mg/dL indicated the importance of DM control quality postoperatively in the prevention of SSI for these patients with trauma. Our data on the perioperative glycemic control were similar to the suggested glycemic control data of studies focusing on elective lower limb surgery for total joint replacement [ 26 , 27 ]. Wexler et al conducted a study in 2008 of 695 patients admitted to an acute care hospital that revealed a prevalence of unrecognized probable diabetes of 18% based on HbA1c levels higher than 6.1%, with 5% of them having HbA1c over 6.5% [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…A preoperative HbA1c of less than 7.850%, with postoperative HbA1c less than 6.650%, preoperative blood glucose less than 130.50 mg/dL, and postoperative blood glucose of less than 148.5 mg/dL indicated the importance of DM control quality postoperatively in the prevention of SSI for these patients with trauma. Our data on the perioperative glycemic control were similar to the suggested glycemic control data of studies focusing on elective lower limb surgery for total joint replacement [ 26 , 27 ]. Wexler et al conducted a study in 2008 of 695 patients admitted to an acute care hospital that revealed a prevalence of unrecognized probable diabetes of 18% based on HbA1c levels higher than 6.1%, with 5% of them having HbA1c over 6.5% [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Preoperative optimization through a dedicated multidisciplinary clinic is a particularly effective means to reduce perioperative complications and improve patient outcomes. The evidence supporting smoking cessation [18], the diagnosis and management of diabetes [19,20], and the correction of anemia [21e23] is robust. Optimization of additional modifiable risk factors may provide further benefit; however, evidence in this area is still growing [24e26].…”
Section: Bodymentioning
confidence: 99%
“…[15][16][17][18][19][20] These concerns are based on the association of diabetes mellitus with elevated postoperative glucose (defined as .194 21 or 200 22 mg/dL) and superficial and deep tissue infections. 19,23 In the current arthroplasty optimization paradigm, most of the orthopaedic surgeons set expectations for meeting HgA1C cutoffs 16,[24][25][26][27][28][29] (ranging from less than 7 to less than 8, which we found varied across institutions we interviewed). Of note, the literature is inconsistent in demonstrating a correlation between HgA1C levels and postoperative complications.…”
mentioning
confidence: 99%
“…The Proceedings of the Second International Consensus Meeting on Musculoskeletal Infection identified a glucose .200 mg/L or a HgA1C .7% as risk factors for periprosthetic joint infection, 27,30 and this result is supported by multiple peer-reviewed studies. 16,[24][25][26]28,29 However, several studies have demonstrated that HgA1C cutoffs alone do not account for increased risk of infection. 21,[31][32][33] There are other metabolic factors such as the requirement for insulin versus oral treatment and postoperative hyperglycemia, which play a role.…”
mentioning
confidence: 99%